Synthesis, Structural Characterization, Thermal properties and Biological Activity of New Complexes Derived from Ligands with N, O Donor Atoms - Nihad Kadhum Hasan (Journal of Global Pharma Technology, 2019)
The study includes preparation and characterisation of a new tridentate Mannich -β-amino carbonyl ligand and its metal complexes are reported. The formation of the ligand (R)-2-((4-(dimethylamino)phenyl) ((2-nitrophenyl)amino)methyl)-5,5-dimethylcyclohexane-1,3-dione (HL) was achieved from the reaction of 4-dimethylaminobenzaldehyde, 2-nitroaniline and dimedone in a 1:1:1 mole ratio, respectively.The reaction of the ligand with Co(II), Ni(II) and Cu(II) metal ions in a 2:1 (L:M) mole ratio resulted in the isolation of monomeric complexes. The ligand and its metal complexes were characterised using a range of analytical and spectroscopic techniques including; elemental microanalysis, magnetic susceptibility, conductance, TGA, FT-IR, electronic spectra and 1H, 13C-NMR spectra. The characterisation data indicated the isolation of six coordinate monomeric complexes with the general formula; [M(HL)2] (where M= Co(II), Ni(II) and Cu(II)). The ligand and its complexes were screened against several bacterial strains and fungi species. The obtained data indicated that the complexes are more active against several kind of organism, under survey, compared with the free ligand.Keywords: Dimedone; Mannich -β-amino carbonyl ligand; Monomeric metal complexes; Thermal properties; Structural study.